Sistem Pemantau Suhu Cooler Box Berbasis Telemetri Dengan Thermoelectric Cooler Sebagai Bakteriostatik Pada Ikan - Yudianto, Renangga; Yudhana, Anton (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2022)
Indonesia has enormous marine resource potential, which can be explored as a prime mover of national economic development, one of which is fisheries resources. The factor that determines the selling value of fish is the freshness of the fish. This study aims to utilize Thermoelectric Cooler (TEC) in cooler boxes as a bacteriostatic system for fish that is environmentally friendly and monitored using telemetry based DS18B20 ESP8266 temperature sensor. The temperature data includes the temperature of the cooler box, the temperature of the Thermoelectric Cooler (TEC), and the temperature of the room. The parameters used to test the quality of DS18B20 temperature sensor are accuracy, normality test, homogeneity test, and independent samples t-test. The data of DS18B20 temperature sensor system is processed at nodeM-CU then sent and displayed via the thingspeak website and LCD in real time. Organoleptically, the obser-vation results of fish A placed in a cooler box are categorized as fresh, and the observation results of fish B which are placed at room temperature are categorized as not fresh according to (SNI 2729:2013). The sensor test results obtained in this study showed value of the temperature accuracy of cooler box was 97.8%, the temperature accuracy value of Thermoelectric Cooler (TEC) was 98.56%, the room tempera-ture accuracy value was 99.67%, the results of normality test of three temperature sensors are normally distributed, the results of homogeneity test of three temperature sensors are homogeneous, and the results of independent samples t-test are not significantly different, which indicates that three DS18B20 tempera-ture sensors are accurate.